2018
DOI: 10.1111/age.12643
|View full text |Cite
|
Sign up to set email alerts
|

A splice site variant in the SUV39H2 gene in Greyhounds with nasal parakeratosis

Abstract: Hereditary nasal parakeratosis (HNPK), described in the Labrador Retriever breed, is a monogenic autosomal recessive disorder that causes crusts and fissures on the nasal planum of otherwise healthy dogs. Our group previously showed that this genodermatosis may be caused by a missense variant located in the SUV39H2 gene encoding a histone 3 lysine 9 methyltransferase, a chromatin modifying enzyme with a potential role in keratinocyte differentiation. In the present study, we investigated a litter of Greyhounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…Up-regulation of stress-induced p53 targets further highlights that the premature exit from the cell cycle occurs on a background of progressive genomic instability and a senescence-like state. This collective phenotype agrees with the severe histological alterations in HNPK nasal epidermis (Bannoehr et al, 2020;Bauer et al, 2018;Jagannathan et al, 2013;Pagé et al, 2003).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Up-regulation of stress-induced p53 targets further highlights that the premature exit from the cell cycle occurs on a background of progressive genomic instability and a senescence-like state. This collective phenotype agrees with the severe histological alterations in HNPK nasal epidermis (Bannoehr et al, 2020;Bauer et al, 2018;Jagannathan et al, 2013;Pagé et al, 2003).…”
Section: Resultssupporting
confidence: 85%
“…Affected homozygous mutant dogs exhibit crusts and fissures of the nasal planum, which suggests a role of SUV39H2 in keratinocyte differentiation and formation of cornified sealing. Support for a causal role of loss of SUV39H2 function in HNPK was further provided by a comparable HNPK phenotype in greyhounds with an independent SUV39H2 splice-site variant with predicted loss of function ( Bauer et al, 2018 ). These observations suggested that H3K9me3 chromatin modifications introduced by SUV39H2 have a high impact on the homeostatic program of keratinocytes.…”
Section: Introductionmentioning
confidence: 97%
“…Hereditary nasal parakeratosis (HNPK) is an inherited disorder in Labrador Retrievers (LR) which has been recognized for more than 15 years [1,2]. Recently, the same clinical and histological presentation of HNPK was described in Greyhounds [3]. Based on pedigree analysis of affected dogs, an autosomal recessive mode of inheritance was determined in LR dogs [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It was earlier demonstrated that the reported N324K variant in the evolutionary conserved SET domain of SUV39H2 leads to an inactive SUV39H2 enzyme [6], thus implying a functional role of this variant in HNPK. Interestingly, HNPK in Greyhounds was associated with a splice site variant in the SUV39H2 gene [3]. SUV39H2 encodes a histone 3 lysine 9 trimethyl (H3K9me3) transferase, which belongs to the large family of lysine methyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…However, for some genes associated with skin disease, the function and anatomic location of the expressed proteins are unknown. Examples for this are SUV39H2 variants in nasal parakeratosis or FAM83G variants in hereditary footpad hyperkeratosis [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%